2019
DOI: 10.1097/sla.0000000000002685
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 2A Receptor Activation Attenuates Ischemia Reperfusion Injury During Extracorporeal Cardiopulmonary Resuscitation

Abstract: Using a novel and clinically relevant porcine model of circulatory arrest and ECPR, we demonstrated that a selective A2AR agonist significantly attenuated systemic IRI and warrants clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 46 publications
(109 reference statements)
0
10
0
1
Order By: Relevance
“…They found that IRI to DMECs was significantly attenuated by ischemic postconditioning or agonism of A 2A receptors and, inversely worsened by its antagonism. In agreement, agonism of A 2A receptors can also attenuate IRI in a porcine model of extracorporeal cardiopulmonary resuscitation by lowering the lactate peak after reperfusion, as well as the markers of inflammation and liver and kidney stress [211]. Selective antagonism of A 2A has been, however, frequently shown to achieve protective outcomes [212,213,214].…”
Section: Therapeutics: the Pharmacological Approachmentioning
confidence: 91%
“…They found that IRI to DMECs was significantly attenuated by ischemic postconditioning or agonism of A 2A receptors and, inversely worsened by its antagonism. In agreement, agonism of A 2A receptors can also attenuate IRI in a porcine model of extracorporeal cardiopulmonary resuscitation by lowering the lactate peak after reperfusion, as well as the markers of inflammation and liver and kidney stress [211]. Selective antagonism of A 2A has been, however, frequently shown to achieve protective outcomes [212,213,214].…”
Section: Therapeutics: the Pharmacological Approachmentioning
confidence: 91%
“…16−22 The molecular mechanisms of adenosine-mediated protection in the setting of pulmonary IRI has been extensively studied by our group. 23,24 Lung protection by A 2A R agonists is mediated primarily by suppressing an inflammatory cascade that is initiated by the activation of iNKT cells, 8 as well as by additional effects to inhibit oxidative burst in neutrophils, platelet aggregation, 25 and inflammatory cytokine release from myeloid cells. 26−28 Based on numerous pre-clinical studies by our group and others, we hypothesize that a Food and Drug Administration (FDA)−approved adenosine A 2A R agonist, regadenoson (Lexiscan, Astellas Pharma US, Inc., Northbrook, IL), administered to lung recipients immediately before transplantation will attenuate IRI.…”
mentioning
confidence: 99%
“…11 Further investigation is warranted to elucidate cellular pathways precipitating functional decline and the potential impact of pharmaceuticals aimed at mitigating ischemia-reperfusion injury. 12,13 It is reassuring to know this technology can support long-distance travel and positive outcomes can be achieved with OCS time greater than 17 h, especially in an organ meeting extended criteria donor status. 6,14 Finally, it cannot be understated how important donor selection is.…”
Section: Commentarymentioning
confidence: 99%
“…Ex vivo perfusion technology will continue to help with the long‐distance transplant but is still imperfect as evidence in translational models where myocardial function deteriorates over time 11 . Further investigation is warranted to elucidate cellular pathways precipitating functional decline and the potential impact of pharmaceuticals aimed at mitigating ischemia‐reperfusion injury 12,13 . It is reassuring to know this technology can support long‐distance travel and positive outcomes can be achieved with OCS time greater than 17 h, especially in an organ meeting extended criteria donor status 6,14 .…”
Section: Commentarymentioning
confidence: 99%